Hypovitaminosis D and effect of vitamin D supplementation in type 2 diabetes mellitus: a rural population based study - Janakiraman, Sathiyanarayanan; Subramanian, Girija (International Journal of Advances in Medicine, 2019)
Background: Deficiency of Vitamin D in general population and its association with various disease conditions have been studied worldwide. Type 2 Diabetes mellitus is increasing at an alarming rate in Indian subcontinent, contributing to increased morbidity and mortality. This study aimed to estimate level of Vitamin D and its association with patients with type 2 diabetes mellitus of rural origin. This study objective was to estimate the Vitamin D level of patients with Type 2 Diabetes mellitus and the effect of Vitamin D supplementation on glycemic status Methods: This study was conducted at the Department of General medicine for a period of 1 year. Eighty patients with type 2 Diabetes mellitus were recruited in the study and baseline parameters of glycemic control and Vitamin D levels were assessed. Only 36 patients complied with the recommendation and evaluated further. Results: All the patients included in the study had insufficient or deficient levels of Vitamin D. The mean vitamin D levels before and after supplementation were 17.75±6.30 and 29.33±6.34 respectively. The mean plasma HbA1c level before and after supplementation were 7.78 and 7.30 respectively. Patients after vitamin D replacement showed significant improvement in their glycaemic status. Conclusions: Vitamin D supplementation of 2000 IU/day had shown to improve the glycaemic status. The beneficial effect of Vitamin D on diabetes was evident in a short period of supplementation.